Is self-generated thought a means of social problem solving? - Ruby, Florence J.; Smallwood, Jonathan; Sackur, Jerome; Singer, Tania (Frontiers in Psychology, 2013)
Appropriate social problem solving constitutes a critical skill for individuals and may rely on processes important for self-generated thought (SGT). The aim of the current study was to investigate the link between SGT and social problem solving. Using the Means-End Problem Solving task (MEPS), we assessed participants’ abilities to resolve daily social problems in terms of overall efficiency and number of relevant means they provided to reach the given solution. We also asked participants to perform non-demanding choice reaction time task (CRT) and a moderately demanding working memory task (WM) as a context in which to measure individuals’ SGT (assessed via thought sampling). We found that although overall SGT was associated with lower MEPS efficiency, it was also associated with higher relevant means, perhaps because both depend on the capacity to generate cognition that is independent of the here and now. The specific content of SGT did not differentially predict individual differences in social problem solving, suggesting that the relationship may depend on SGT regardless of its content. In addition, we also found that performance at the WM but not the CRT was linked to overall better MEPS performance, suggesting that individuals good at social processing are also distinguished by their capacity to constrain attention to an external task. Our results provide novel evidence that the capacity for SGT is implicated in the process by which solutions to social problems are generated, although optimal problem solving may be achieved by individuals who display a suitable balance between SGT and cognition derived from perceptual input.